COVID-19 infection prevention and control procedures and institutional trust: Perceptions of Palestinian healthcare workers - El Sharif, Nuha; Ahmead, Muna; Imam, Asma (Frontiers in Public Health, 2022)
Background Lack of trust in institutional control measures during Coronavirus disease 2019 (COVID-19) outbreaks may affect healthcare workers' (HCWs) levels of stress and wellbeing, and as a consequence, may influence their trust and confidence in their organization. This study aims to understand factors associated with healthcare workers perceptions of trust in organizational preparedness, communication, and infection risk during the COVID-19 pandemic. Methods A cross-sectional study was conducted among HCWs (n = 876) in 16 COVID 19 healthcare facilities between October and December 2020 in Palestine (Gaza Strip, West Bank and East Jerusalem). A stratified purposive sample using an online self-administered Arabic version of a questionnaire was used for data collection. The questionnaire used for this study was adapted from the World Health Organization Blueprint Novel Coronavirus Perceptions of healthcare workers regarding local infection prevention and control procedures for a COVID-19 research protocol. Data were analyzed using Statistical Package for Social Sciences software version 23. In the bivariate analysis, T-test, one-way ANOVA and χ2 test were used at a significant p-value < 0.05. In the multivariable logistic regression analyses, the adjusted odds ratios and its 95% confidence intervals are presented. Results Findings showed that confidence in the systems' ability to manage COVID-19 cases, encouragement and support from senior medical/nursing staff to apply recommended IPC measures, and good levels of mental health increased trust in the organization. Additionally, receiving proper training on IPC procedures for other communicable diseases, having access to clear policies and procedures related to IPC procedures for COVID-19, and providing PPE during the previous clinical shift also increased trust. However, the intention to use recommended PPE when treating patients with suspected or confirmed COVID-19 when having access to it and feeling emotional was negatively correlated with this trust. Conclusions HCWs should be provided with clear, accessible communications about policies and protocols, as well as training about infection prevention and control, personal protective equipment, and support during pandemics to increase their trust in the healthcare system. Additionally, the improvement in HCWs' wellbeing can be attributed to a greater sense of trust in institutions.